The seas divide geopolitics and maritime issues in Southeast Asia - Sidhu, Jatswan S. 1962-; Balakrishnan, K. S. (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2008)
[The book] addresses an array of maritime security concerns currently affecting the Southeast Asia region. Maritime security is threatened not only by the presence of sizeable navies but border and territorial issues as well. As such, pressure on the need for better military intelligence is on the increase. In addition, some of the security concerns like piracy, smuggling, environmental considerations, developments in contemporary maritime law, fisheries disputes, regional naval equation and military technological changes are all having an impact on maritime geopolitics and security in one way or another. Are regional countries fully prepared for the future is another question that remains to be investigated? In sum, this work attempts to look at the main strategic concerns of Southeast Asia in its maritime zone.